Sociodemographic Variables of Hepatitis C Positive Cases among Pregnant Women Admitted in Tertiary Care Hospital - Anwer, Qudsia; Hassan, Summaira; Jabeen, Salma; Ahmed, Afzaal; Waheed, Faryal; Saeed, Shanawer (Indus Journal of Bioscience Research, 2025)
Background: Hepatitis C virus (HCV) infection is one of the most prevalent chronic blood-borne infections globally and poses a significant public health challenge. Vertical transmission, where the virus is passed from mother to child, is a key route of HCV spread. Several factors including educational status, geographic location, socioeconomic background, and the timing of medical presentation, contribute significantly to maternal transmission of the virus. In southern Punjab, there is a lack of comprehensive research on the demographic factors influencing HCV prevalence. So the objective of the study was to assess the socio demographic variables of hepatitis C in pregnant women coming for antenatal visit in tertiary care hospital Bahawal Victoria Hospital Bahawalpur. Methods: A cross-sectional descriptive study was conducted in Gynecological and Obstetric wards Bahawal Victoria Hospital, Bahawalpur, for the duration of six months, from January 2024 to June 2024. The calculated sample size was 168. A predesigned and pretested questionnaire was used, the questionnaire included basic information like maternal age, parity, area of residence, socioeconomic status, mode of past deliveries, history of blood transfusion, needle sharing and any past surgical history. Data was entered and analyzed by using statistical package for social sciences (SPSS) version 23. Results: The mean age of the participants was 28±5.4 years. About 46 (27.4%) respondents belong to lower class, 81 (48.2%) were middle class while 41 (24.4%) were from upper class. It was found that most respondents 101(60.1%) belong to an urban residential area, while 67 (39.9%) were from the rural residential area. Majority (58.3%) participants were having more than 6 living children. Blood transfusion as a significant factor for hepatitis C, was positive in 78.8% of respondents. About 103(61.3%) participants had history of previous C-section. Another factor history of surgery other than C-section in past was 6.5%. Respondents were also inquired about another factor “needle sharing”. It was found that only 3 (1.8%) participants found history of needle sharing. Only 5 (2.9%) cases gave history of parenteral drug abuse. Conclusion: The most commonly noted risk factors were history of blood transfusion (78.8%) and history of C-section (61.3%) while other factors including past surgical history (6.5%), history of needle sharing (1.8%) and history of parenteral drug abuse (2.9%). There is a need of public education and awareness regarding spread of hepatitis C infection, beside that implementing universal screening during pregnancy is advisable to reduce potential complications associated with the infection.